Phono-Stylistic Analysis of John Lennon's Stand by Me: Unveiling the Sound of Solidarity - Br Sembiring, Franinta Egia D. R; Br Sembiring, Pemina; Rahmadsyah Rangkuti (Vivid: Journal of Language and Literature, 2025)
This study investigates the phonostylistic features of John Lennon’s 1975 rendition of Stand by Me, focusing on how vocal elements such as consonants, vowels, pitch, rhythm, and stress patterns contribute to the emotional depth and thematic complexity of the song. The pokok masalah of this research is understanding how phonetic choices shape the song’s expression of solidarity, vulnerability, and resilience, and how these themes are reinforced through vocal dynamics. The tujuan of this study is to examine how phonostylistic features enhance the song’s message of unwavering support and emotional connection. The metode used is a qualitative phonostylistic analysis, which involves analyzing the consonantal and vowel patterns in the lyrics, identifying key phonetic elements, and examining their relationship with the song's emotional and thematic impact. The data is derived from transcriptions of the song’s lyrics, focusing on prominent consonants and vowels, as well as shifts in pitch, rhythm, and vocal stress. The analysis reveals that the repetition of key words such as “stand,” “night,” and “I” amplifies the song’s central message of support and connection. The study concludes that Lennon’s vocal delivery not only intensifies the song’s emotional resonance but also transforms Stand by Me into a timeless symbol of collective strength and solidarity, continuing to resonate across generations.